Allergy‐related diseases and recurrent abdominal pain during childhood – a birth cohort study. Issue 11 (1st October 2014) - Olén, O.; Neuman, Å.; Koopmann, B.; Ludvigsson, J. F.; Ballardini, N.; Westman, M.; Melén, E.; Kull, I.; Simrén, M.; Bergström, A.
Summary: Background: Allergy and immune dysregulation may have a role in the pathophysiology of recurrent abdominal pain of functional origin, but previous studies of allergy‐related diseases and abdominal pain have contradictory results. Aim: To examine the association between allergy‐related diseases or sensitisation during childhood and abdominal pain at age 12 years. Methods: In this birth cohort study of 4089 children, parents answered questionnaires regarding asthma, allergic rhinitis, eczema and food hypersensitivity ('allergy‐related diseases') at ages 0, 1, 2, 4, 8 and 12 years. Blood for analyses of allergen‐specific IgE was sampled at 4 and 8 years. At 12 years, the children answered questions regarding abdominal pain. Children with coeliac disease or inflammatory bowel disease were excluded. Associations were examined using multivariable logistic regression. Results: Among 2610 children with complete follow‐up, 9% ( n  = 237) reported abdominal pain at 12 years. All allergy‐related diseases were associated with concurrent abdominal pain at 12 years and the risk increased with increasing number of allergy‐related diseases ( P for trend <0.001). Asthma at 1 and 2 years and food hypersensitivity at 8 years were significantly associated with abdominal pain at 12 years. There was an increased risk of abdominal pain at 12 years in children sensitised to food allergens at 4 or 8 years, but in stratified analyses, this was confined to children whose parents had not reported food hypersensitivity at time of sensitisation. Conclusion: Allergy‐related diseases as well as sensitisation to food allergens were associated with an elevated risk of abdominal pain, and the risk increased with the number of allergy‐related diseases.